Cultivating Global Citizenship through Higher Education: A Reflection on the Development from Civic to Global Engagement - Johanna M. Grad; Indira S.E. van der Zande (MDPI AG, 2022)
Due to globalization, society underwent changes towards multiculturalism and vast internationalization of the labor market. Those changes make it necessary to adapt the education of future citizens and equip them with tools to persist in an internationalized and globalized world. Contrary to popular concerns, service and engagement can be connected to the goal of internationalization in higher education. The aim of this theoretical paper is to provide new perspectives on the topic of internationalization in higher education and the development of Global Citizenship. We analyze the existing literature to explore the development and interconnections between different types of engagement, specifically the concepts of Civic Engagement, Service Learning, Global Engagement and Global Service Learning. Subsequently, we discuss the role and relevance of higher education institutions and partnerships in achieving Global Citizenship by equipping students with the cross-cultural competencies they need to be successful in a global society. Finally, we discuss the merit of Global Learning and the role engagement can play in the future of internationalized and engaged education.